Balance and main challenges of the current style of costa rican growth in economic, social and environmental matters - Andrés Zamora Bolaños, Edwin (2024)
The economic crisis of the 1980s, followed by the subsequent Stabilization and Structural Adjustment Programs, marked the beginning of a new style of development in Costa Rica, based on Export Promotion, the Attraction of Foreign Direct Investment (FDI) and a reduced role of the State in the economy. Despite the fact that the new style of growth has allowed the country to enjoy some macroeconomic stability measured through a stable balance of payments, inflation and exchange rates, the country has not been able to overcome the great lags resulting from the crisis of the 1980s, and continues to face great challenges in terms of poverty and inequality,  as well as the fiscal deficit, the latter paradoxically aggravated by the same policies to promote exports and attract investment implemented in the country; based on tax incentives that do not favour the stability of public finances. Currently, the country also faces challenges associated with the unsustainable use of environmental resources, such as water resource management, poor planning in land use and abuse in the consumption of agrochemicals.